Hogar del Buen Vivir: Equipamiento para el Adulto Mayor en la Ciudad de Neiva-Huila Categoría: Proyecto Arquitectónico - Subcategoría: Proyecto Arquitectónico (2022)
The present work deals with the proposal of a Home for Good Living: equipment for the elderly in the city of NeivaHuila, taking into account that the fact of living to an advanced age is a privilege, but it is not exempt from challenges. : one of the greatest tensions will occur in the area of care for the elderly, because as this happens, the propo rtion of people with difficulties for the normal development of their daily activities increases, they need the help and care of others . It has been identified that in Colombia there is a lack of spaces or residences for older adults, where they can atten d even before they begin to present problems in the physical or mental health of these people. Therefore, this work seeks to answer the following question: How to implement a specialized Geriatric Center with new sustainable technologies which covers its u scale for older adults in the city of Neivase on an urban Huila? For which we work based on the general objective: Develop architectural proposal for a specialized geriatric center to guarantee a healthy life and promote the wellbeing of the elderly in Neiva.